Peningkatan kemampuan pemecahan masalah matematis siswa SMP melalui model problem based learning: Studi kuasi eksperimen pada materi bilangan bulat - Yeyen Nuraeni; Indah Puspita Sari; Risma Amelia (IKIP Siliwangi, 2026)
This research examines the impact of the Problem-Based Learning (PBL) model on students' mathematical problem-solving proficiency in the context of integers. Adopting a quasi-experimental design, 54 seventh-grade students were assigned to either an experimental or control group. Statistical analysis—including normality, homogeneity, N-gain, and independent t-tests—indicated that the experimental group significantly outperformed the control group (N-gain of 0.84 vs. 0.54; p < 0.05). These findings suggest that implementing the PBL model provides a more effective pedagogical alternative to conventional methods for improving students' mathematical problem-solving skills.